Millennium : Jahrbuch zu Kultur und Geschichte des ersten Jahrtausends n. Chr. / Yearbook on the Culture and History of the First Millennium C.E. (De Gruyter, 2004)
Millennium pursues an interdisciplinary international approach transcending epochal boundaries to research the first millennium AD. The editorial board and the advisory board represent a wide range of disciplines - contributions from art and literary studies are published alongside historical, theological and philosophical contributions on the Latin, Greek and the Oriental cultures.